2023
DOI: 10.3389/fpsyt.2023.1148534
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the conversational agent with an emotional support system for mental health digital therapeutics

Abstract: As psychological diseases become more prevalent and are identified as the leading cause of acquired disability, it is essential to assist people in improving their mental health. Digital therapeutics (DTx) has been widely studied to treat psychological diseases with the advantage of cost savings. Among the techniques of DTx, a conversational agent can interact with patients through natural language dialog and has become the most promising one. However, conversational agents' ability to accurately show emotiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Prior studies, such as the work of Valtolina and Hu (2021), have demonstrated the potential of AIbased conversational agents in providing social support and mitigating feelings of loneliness among older adults. This is further evidenced by the findings of Jones et al (2021), indicating the effectiveness of an AIbased conversational agent in reducing loneliness within a retirement community, and Wang et al (2023), highlighting the positive impact on individuals with mental health conditions.…”
Section: Discussionmentioning
confidence: 73%
“…Prior studies, such as the work of Valtolina and Hu (2021), have demonstrated the potential of AIbased conversational agents in providing social support and mitigating feelings of loneliness among older adults. This is further evidenced by the findings of Jones et al (2021), indicating the effectiveness of an AIbased conversational agent in reducing loneliness within a retirement community, and Wang et al (2023), highlighting the positive impact on individuals with mental health conditions.…”
Section: Discussionmentioning
confidence: 73%
“…Our study ventured into the relatively unexplored field of digital therapeutics (DTx), emphasizing the influence of a virtual agent on usability and therapeutic outcomes-a synergy suggested by prior research [6]. Through a month-long longitudinal study, we provided concrete data on how the agent's design features correlate with therapeutic efficacy and usability.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly in DTx, where long-term use and digital therapeutic alliance, which can be referred to as the relationship between DTx and user, are crucial, the importance of agents is accentuated, given the fact that agents can boost digital alliance [5]. Furthermore, in the prevalent digital therapeutics field of mental healthcare, enhancing sociability to foster agent-user relationships and emotional support added a secondary benefit [6]. Numerous prior studies have thus provided insights into the design and role of agents in the digital healthcare field.…”
Section: Introductionmentioning
confidence: 99%